Influence of fibre length on properties of glass-fibre reinforced bark particleboards : Utjecaj duljine vlakana na svojstva iverice od kore ojačane staklenim vlaknima - Pásztory, Zoltan (Array, 2020)
This study was carried out to assess the feasibility of glass fibres of various lengths (12 mm, 18 mm, 24 mm and 30 mm) as reinforcement on the mechanical performance of bark particleboards intended for thermal insulation. To evaluate their efficiency, the results of fibre reinforced particleboards at mass of 3wt% concentration were compared with plain bark based boards. Thermal, physical and mechanical properties (modulus of rupture, modulus of elasticity and internal bond) were determined on unreinforced and reinforced specimens. In general, the results of the thermal conductivity measurements indicated that the bark panels could potentially be used as feedstock for thermal insulation panels. However, the glass fibres lengths had a direct adverse effect on the mechanical behaviour of the bark particleboard, instead of providing synergistic reinforcement. Furthermore, the static bending properties, mainly the modulus of rupture, gradually decreased with increasing lengths of glass fibre.